Emerging threat of artemisinin partial resistance markers (pfk13 mutations) in Plasmodium falciparum parasite populations in multiple geographical locations in high transmission regions of Uganda - Bosco B. Agaba; Jye Travis; David Smith; Simon P. Rugera; Maria G. Zalwango; Jimmy Opigo; Charles Katureebe; Ruth Mpirirwe; Dembo Bakary; Martin Antonio; Beshir Khalid; Joseph Ngonzi; et al. (Malaria Journal)
Abstract Background Artemisinin-based combination therapy (ACT) is currently recommended for treatment of uncomplicated malaria. However, the emergence and spread of partial artemisinin resistance threatens their effectiveness for malaria treatment in sub-Saharan Africa where the burden of malaria is highest. Early detection and reporting of validated molecular markers (pfk13 mutations) in Plasmodium falciparum is useful for tracking the emergence and spread of partial artemisinin resistance to inform containment efforts. Methods Genomic surveillance was conducted at 50 surveillance sites across four regions of Uganda in Karamoja, Lango, Acholi and West Nile from June 2021 to August 2023. Symptomatic malaria suspected patients were recruited and screened for presence of parasites. In addition, dried blood spots (DBS) were collected for parasite genomic analysis with PCR and sequencing. Out of 563 available dried blood spots (DBS), a random subset of 240 P. falciparum mono-infections, confirmed by a multiplex PCR were selected and used for detecting the pfk13 mutations by Sanger sequencing using Big Dye Terminator method. Regional variations in the proportions of pfk13 mutations were assessed using the chi square or Fisher’s exact tests while Kruskal–Wallis test was used to compare absolute parasite DNA levels between wild type and mutant parasites. Results Overall, 238/240 samples (99.2%) contained sufficient DNA and were successfully sequenced. Three mutations were identified within the sequenced samples; pfk13 C469Y in 32/238 (13.5%) samples, pfk13 A675V in 14/238 (5.9%) and pfk13 S522C in (1/238 (0.42%) samples across the four surveyed regions. The prevalence of pfk13 C469Y mutation was significantly higher in Karamoja region (23.3%) compared to other regions, P = 0.007. The majority of parasite isolates circulating in West Nile are of wild type (98.3), P = 0.002. Relative parasite DNA quantity did not differ in samples carrying the wild type, C469Y and A675V alleles (Kruskal–Wallis test, P = 0.6373). Conclusion Detection of validated molecular markers of artemisinin partial resistance in multiple geographical locations in this setting provides additional evidence of emerging threat of artemisinin partial resistance in Uganda. In view of these findings, periodic genomic surveillance is recommended to detect and monitor levels of pfk13 mutations in other regions in parallel with TES to assess potential implication on delayed parasite clearance and associated treatment failure in this setting. Future studies should consider identification of potential drivers of artemisinin partial resistance in the different malaria transmission settings in Uganda.